Increases in microcrustaceans (Cladocera and Copepoda) associated with phytoplankton peaks in tropical reservoirs - Perbiche-Neves, Gilmar; Portinho, Jorge Laço [UNESP]; Ferreira, Rosa Antônia Romero [UNESP]; Nogueira, Marcos Gomes [UNESP] (My University, 2016)
We studied the interactions between microcrustaceans and phytoplankton in storage and run-of-river tropical cascade reservoirs in Brazil by performing comparisons on a spatial-temporal scale and non-parametric correlations. Samples of zooplankton and phytoplankton were obtained quarterly over a period of two years from four sites at each reservoir. Cladocerans, such as Daphniidae and Sididae in addition to adult copepods, increased in response to seasonal phytoplankton density peaks in the storage reservoir and also in the areas close to the dam zone of the run-of-river reservoir. The abundances of filter-feeding microcrustaceans and of Cryptophyceae, Chrysophyceae, Cyanophyceae, Chlorophyceae and total phytoplankton were positively correlated. Adult cyclopoids with raptorial feeding habits were particularly correlated with Bacillariophyceae, Chlamydophyceae, Cryptophyceae and Dinophyceae. As expected, fluctuations in the abundances of the phytoplankton classes in both reservoirs could be associated with the differing responses of the filter feeders and raptorial microcrustaceans, with differences observed among the taxonomic groups.
Keywords: Algal quality; Correlations; Crustacea; Paranapanema river; Phytoplankton; Tropical impoundments